Challenges in differential diagnosis between primary and secondary forms of hyperparathyroidism - Natalia G. Mokrysheva (Ожирение и метаболизм, 2017)
Hyperparathyroidism is a disease characterized by excessive secretion of parathyroid hormone (PTH) in the chief cells of parathyroid glands. There are three types of hyperparathyroidism: primary, secondary, and tertiary depending on the cause of this disease. By the secondary hyperparathyroidism calcium-sensing receptors (CaSR) and vitamin D receptors (VDR) lead to disturbance of phosphorus-calcium exchange and to development of a parathyroid glands hyperplasia. Treatment of secondary hyperparathyroidism with vitamin D showed the efficiency not only in normalization of clinical laboratory indicators but also in involution of changes in parathyroid glands. We represent the clinical case of a patient with secondary hyperparathyroidism caused by hypovitaminosis D, parathyroid hyperplasia more than 1 cm. The long-term oral therapy with active vitamin D led to the positive dynamics of PTH levels, as well as complete reduction of parathyroid lesion.